Staging Investigations in Breast Cancer: Collective Opinion of UK Breast Surgeons. (20th November 2013) - Chand, N.; Cutress, R. I.; Oeppen, R. S.; Agrawal, A.
Abstract : Introduction . Certain clinicopathological factors are associated with a higher likelihood of distant metastases in primary breast cancer. However, there remains inconsistency in which patients undergo formal staging for distant metastasis and the most appropriate investigation(s). Aims . To identify UK surgeon preferences and practice with regard to staging investigations for distant metastases. Methods . A survey was disseminated to members of the Association of Breast Surgery by e-mail regarding surgeon/breast unit demographics, use of staging investigations, and local policy on pre/postoperative staging investigations. Several patient scenarios were also presented. Results . 123 of 474 (25.9%) recipients completed the survey. Investigations routinely employed for patients diagnosed with early breast cancer included serological/haematological tests (72% respondents), axillary ultrasound (67%), liver ultrasound (2%), chest radiograph (36%), and computed tomography (CT) (1%). Three areas contributed to decisions to undertake staging by CT scan: tumour size, axillary nodal status, and plan for chemotherapy. There was widespread variation as to criteria for CT staging based on tumour size and nodal status, as well as the choice of staging investigation for the clinical scenarios presented. Conclusions . There remains variation in the use of staging investigations for distant disease in early breastcancer despite available guidelines.